1998
DOI: 10.1111/j.1745-6584.1998.tb01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine WT and Bacillus subtilis Transport through an Alluvial Gravel Aquifer

Abstract: A field study was conducted to characterize the transport of rhodamine WT dye and endospores of the bacterium Bacillus subtilis through preferential flowpaths in an alluvial gravel aquifer using natural gradient tracer experiments. Preliminary tracer experiments were conducted with rhodamine WT to determine preferential flowpaths using a resin bag method, because of spatial heterogeneity at the study site. Rhodamine WT, Cl, and B. subtilis endospores were then injected 0.1 to 1.6 m below the water table, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 26 publications
8
71
0
Order By: Relevance
“…Estimation of D, R, and λ required both first and second normalized moments, which resulted in the observed marked deviation. This observation was found to be consistent with the reports of Leij and Dane (1992) and Pang et al (1998) as cited by Pang et al (2003) where it was noted that the higher the orders of the moments are, the less stable is the calculation. The MOM estimates higher values of R and D when compared with the least squares curve-fitting program.…”
Section: Discussionsupporting
confidence: 81%
“…Estimation of D, R, and λ required both first and second normalized moments, which resulted in the observed marked deviation. This observation was found to be consistent with the reports of Leij and Dane (1992) and Pang et al (1998) as cited by Pang et al (2003) where it was noted that the higher the orders of the moments are, the less stable is the calculation. The MOM estimates higher values of R and D when compared with the least squares curve-fitting program.…”
Section: Discussionsupporting
confidence: 81%
“…They represented bacterial attenuation by an apparent decay constant (incorporating attachment losses as well as true bacterial decay), and estimated values on the order of 1.0 day À1 for coliform bacteria in groundwater. Pang et al [88] describe results of a second experiment in which Rhodamine WT, Cl, and a bacterium were injected below the water table. They observed faster velocities of the bacteria relative to inert tracers, and estimated total removal rates of 2.4-9.4 day À1 .…”
Section: Previous Field-scale Bacterial Transport Experimentsmentioning
confidence: 99%
“…Some researchers claim that the poor tracer mass recovery and the non-conservative character of RWT does not adversely affect the quality of the tracer test results, especially if the method of moments is used for interpretation [6,8,17]. However, if the results interpretation is based on a simulation method that involves fitting the model curve directly to the tracer test results these discrepancies may be important.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature on RWT reactivity, and in particular susceptibility to sorption to sediments, is somewhat conflicting. Some studies [6] consider the RWT as a conservative tracer, whereas other studies [7,8] aimed at comparison of RWT and other conservative tracer such as LiCl and Br suitability in determination of hydraulic characteristics of constructed and natural wetlands, showed that RWT is less stable than LiCl and Br.…”
Section: Rhodamine Wtmentioning
confidence: 99%